An Adaptive Safety Message Transmission Algorithm Based on Age-of-Information and Collision Risk-Level with Adjacent Vehicles in IEEE802.11p/WAVE Vehicular Networks - Choi, Jong Young; Ko, Young Bae (Journal of Korean Institute of Communications and Information Sciences, 2022)
This paper introduces a new concept, named as Collision Risk-Level aware Age-of-Information, which considers a degree of collision risk with adjacent vehicles, in order to improve safety in IEEE802.11p/WAVE vehicular networks. It also proposes an adaptive transmission rate control algorithm for minimizing the AoI of BSMs(Basic Safety Messages) from those adjacent cars. Using the well-known ns-3 simulator, we have implemented the proposed algorithm and analyzed its performance.
Keywords: Age of Information; Basic Safety Message; BSM rate adaptation; Collision Risk Level; IEEE 802.11p/WAVE; road safety; V2V communication; Vehicular networks